Polityczne show jako nowoczesny przykład komunikowania politycznego. Narodziny telewizyjnych debat wyborczych w Wielkiej Brytanii - Rożewska, Agnieszka (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
Three debates involving the leaders of the main political parties in the UK attracted first-time voters in the 2010 elections. The analysis of the Reuters Institute, based on YouGov’s questionnaires, confirmed that the 18–24 age group had shown particular interest in the debates. After the elections, 55% of the young electorate declared that the leaders’ debates had helped them to make up their minds, whereas 92% admitted having exchanged opinions in their circles after the debates. Television debates have thus been shown to have a considerable influence on voters and in particular on first time voters. The very fact that the debates enjoyed such enormous audience interest demonstrates the influence they have on the development of public discourse; political debates have been written about and discussed extensively. They have also undoubtedly become an unforgettable TV spectacle.